Expression of cytokines, chemokines and other effector molecules in two prototypic autoinflammatory skin diseases, pyoderma gangrenosum and Sweet's syndrome. (4th September 2014) - Marzano, A V; Fanoni, D; Antiga, E; Quaglino, P; Caproni, M; Crosti, C; Meroni, P L; Cugno, M
Summary: Pyoderma gangrenosum (PG) and Sweet's syndrome (SS) are two inflammatory skin diseases presenting with painful ulcers and erythematous plaques, respectively; both disorders have a debilitating clinical behaviour and PG is potentially life-threatening. Recently, PG and SS have been included among the autoinflammatory diseases, which are characterized by recurrent episodes of sterile inflammation, without circulating autoantibodies and autoreactive T cells. However, an autoinflammatory pattern clearly supporting this inclusion has never been demonstrated. We studied 16 patients with PG, six with SS and six controls, evaluating, using a sandwich-based protein antibody array method, the expression profile of inflammatory effector molecules in PG, SS and normal skin. The expressions of interleukin (IL)-1 beta and its receptor I were significantly higher in PG ( P = 0·0001 for both) and SS ( P = 0·004–0·040) than in controls. In PG, chemokines such as IL-8 ( P = 0·0001), chemokine (C-X-C motif) ligand (CXCL) 1/2/3 ( P = 0·002), CXCL 16 ( P = 0·003) and regulated upon activation normal T cell expressed and secreted (RANTES) ( P = 0·005) were over-expressed. In SS, IL-8 ( P = 0·018), CXCL 1/2/3 ( P = 0·006) and CXCL 16 ( P = 0·036) but not RANTES were over-expressed, suggesting that chemokine-mediated signals are lower than in PG. Fas/Fas ligand and CD40/CD40 ligand systems were over-expressed in PG ( P = 0·0001 for Fas, P = 0·009 for Fas ligand, P = 0·012 for CD40, P = 0·0001 for CD40 ligand), contributing to tissue damage and inflammation, while their role seems to be less significant in SS. Over-expression of cytokines/chemokines and molecules amplifying the inflammatory network supports the view that PG and SS are autoinflammatory diseases. The differences in expression profile of inflammatory effectors between these two disorders may explain the stronger local aggressiveness in PG than SS.